Systematic Review of Disparities in Access to Physical Therapy Utilizing Text-Mining Techniques - Park, JaeJun (International Journal of Innovative Research in Medical Science, 2022)
Physical therapy and rehabilitative care are highly necessary for the maintenance and recovery of health and well-being. Aside from healing light muscle sprains, physical therapy prevents the development of more post-operative complications down the line. Furthermore, physical therapy allows patients to improve their quality of life and prevents other conditions from occurring. However, in the United States, multiple barriers exist to attaining the level of rehabilitative care due to various social determinants of health (SDH). These determinants play a very big role, especially in physical therapy, which requires patients to visit the clinics consistently, increasing the cost and transportation. Socioeconomic disparities are a very large barrier, due to the low number of private clinics accepting Medicaid or government insurance for low-income patients. Racial barriers also limit access to care, as African-Americans tend to be under-referred by physicians, not being able to receive the necessary care. Further examination of other factors including gender, educational attainment, and geographic location reveal more trends of high barriers in access to physical therapy. This paper seeks to address the question: “How do differences between various social factors and demographic variables affect access to physical therapy care?” By examining the most relevant disparities with machine learning techniques, insight can be gathered for more targeted public health policies and actions to make physical therapy more accessible.